Fibrous epulis: a case report on the management of a massive benign tumor on the right mandible with local anaesthesia - Aji, Bayu Anggoro; Mulato, Agus; Sejati, Bramasto Purbo; Widiastuti, Maria Goreti (Majalah Kedokteran Gigi Indonesia, 2025)
Epulis is a gingival hyperplasia that originates from the connective tissue of the periodontal membrane, caused by chronic irritation. Fibrous epulis presents clinically with or without a stalk; has a pale color, a resilient consistency, well-defined borders, firm texture; does not easily bleed; and does not cause pain. When epulis reaches a significant size, it can interfere with oral cavity function and the patient's nutritional intake. An 82-year-old female patient presented at the oral surgery clinic of RSPAU Hardjolukito with a complaint of a lump on the right mandible. The patient reported that the lump had appeared since the last several months and caused difficulties eating and speaking. Clinical examination revealed a mass with resilient consistency, well-defined borders, firm texture, no tendency to bleed, and no pain, measuring 4.5 x 2.5 x 2.5 cm on the right mandible, preventing the patient from chewing and closing her mouth. The lesion was removed surgically under local anesthesia and histopathological examination findings showed fibromyxoid connective tissue, confirming the definitive diagnosis of fibrous epulis without signs of malignancy. No complications occurred, and the patient reported a significant improvement in the oral cavity function and facial aesthetics. This case highlights the importance of early identification and appropriate management to achieve good outcomes with minimal risk. Excision with local anesthesia is a safe option to avoid the risks associated with general anesthesia.